ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN USAHA NELAYAN DI KABUPATEN TAKALAR - Achsanuddin UA, Anur (Perpustakaan dan Penerbitan Unismuh Makassar, 2017)
This study aims to determine and analyze the factors that affect the income level of fishermen in Takalar District. The data used is the primary data with the number of respondents 50 people. The variables in this research are working capital, labor, work experience and technology as independent variable and income of fisherman business as dependent variable. Hypothesis testing is done bymultiple linear regression analysis.The results of this study indicate working capital, labor, work experience, and technology significantly affect the income of fishermen in Takalar District